2016
DOI: 10.3906/tar-1603-45
|View full text |Cite
|
Sign up to set email alerts
|

Quality traits of green plums (Prunus cerasifera Ehrh.) at different maturity stages

Abstract: Introduction Plums (Prunus spp.) are well adapted to a broad range of ecogeographic conditions, as shown by the diversity of species worldwide. In Turkey, the identified species include Prunus cerasifera Ehrh., Prunus domestica L.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 25 publications
3
12
1
Order By: Relevance
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…Mert and Erturk (2017) reported the crude fat amount chestnut cultivars ranged from 0.87 to 2.61%. Our results are in accordance with those obtained by Erturk et al (2006) for C. sativa and hybrid cultivars, for Italian cultivars (Sacchetti and Pinnavaia, 2005) and for Spanish cultivars (De La Montana Miguelez et al, 2004 andPereiraLorenzo et al, 2006) Previous studies indicated cultivar/genotype differences on chemical content of fruit species, including stone fruits, nuts, berries and subtropical fruits (Celik et al, 2007;Ercisli, 2009;Ercisli et al, 2010;Erturk et al, 2010;Saridas et al, 2016;Yazici and Sahin, 2016;Zorenc et al, 2016).…”
Section: Proximate Compositionsupporting
confidence: 81%
“…They are genetically a very diverse group and play a major role in modern society and economy. Fruit and vegetables are an important component of traditional food but are also central to healthy diets of modern urban populations (Hricova et al, 2016;Sakar et al, 2016;Saridas et al, 2016;Solmaz et al, 2016). Sea buckthorn, a thorny deciduous shrub with a distinctive tolerance to drought, cold, and salinity, is naturally distributed over Asia and Europe (Jain et al, 2010).…”
mentioning
confidence: 99%
“…The levels of bioactive compounds vary between fruit Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 7:41 AM species, genotypes, accessions, and also between different environmental conditions (temperature, soil, water, etc. ) (Mikulic-Petkovsek et al 2015, Saridas et al 2016, Yazici and Sahin 2016, MikulicPetkovsek et al 2017 Wild edible fruits show a rich biodiversity, which forms the basis for human survival and economic well-being, and constitutes the resources upon which families, communities, nations and future generations depend (Singh et al 1994). They are harvested from forests and marginal lands of rural areas without commercial cultivation.…”
Section: Introductionmentioning
confidence: 99%